Revealed informal activity - Ralitza Dimova; Ira N. Gang; John Landon-Lane (Institute for the Study of Labor (IZA), 2011)
What does it mean to be in the informal sector? Many characterizations have been used in the literature, for example, firms that are unregistered or employ a small workforce or firms/economic enterprises that do not have access to formal capital markets. But many people participate in both formal and informal activities, while classification of participation is often based on primary employment. This creates limitations to the analytical power of existing measures of informality. We develop a method for assigning households to the informal sector by inferring informal sector activity using income and expenditure surveys. We apply this method to the case of Bulgaria using LSMS income and expenditure surveys before and after a significant economic reform and compare it to those made using other indicators of informal sector activity. Our work shows that the informal sector acts as a buffer for households during periods of crisis when formal sector employment opportunities are limited. It shows the limitations of alternative stylized measures of informality in assessing the vulnerability of households involved in the informal sector, especially during periods of extreme economic hardship.
urn:nbn:de:101:1-201104134451
Keywords: O17; 330; informal labour markets; crisis; Bulgaria; Informeller Sektor; Privater Haushalt; Übergangswirtschaft; Wirtschaftskrise; Haushaltsbudget-Statistik; Bulgarien